Introduction to maternity & pediatric nursing - Leifer, Gloria (Saunders, 2003)
Part of the popular LPN Threads series, this market-leading text provides coverage of basic maternity and pediatric nursing in one convenient text. Material is presented with a logical and effective simple-to-complex and health-to-illness organization. With an emphasis on prevention, early recognition, and the family, this edition also includes enhanced coverage of antepartum care and a new full-color design.